Enhancing Administrative Autonomy within the Ministry of National Education in Madagascar by Reducing Political Influence - Whega Danitsaike Bien-Aimé; Rabibisoa Giovanni; Ravaoarisoa Simonette Augustin (Universitas Islam Negeri Mataram, 2026)
This study aims to examine the extent of administrative autonomy within the Ministry of National Education in Madagascar and to analyze how political influence shapes administrative practices, decision-making processes, and education governance outcomes. The study adopts a qualitative design based on semi-structured interviews and document analysis. Data were collected from 20 purposively selected key informants, including senior ministry officials, mid-level administrators, school inspectors, policy advisors, members of the National Assembly, and education experts. Thematic analysis was employed to identify patterns related to administrative autonomy, political influence, and governance constraints. The findings reveal that political interference significantly limits administrative autonomy, particularly in personnel management, budgeting, and policy implementation. Weak legal safeguards and ambiguous institutional roles intensify administrative dependence on political actors. Professional capacity and informal depoliticization strategies partially mitigate political pressure but remain insufficient to ensure sustained institutional autonomy. This study contributes original empirical evidence on ministerial-level administrative autonomy in a low-income, politically fragile context. By focusing on the central education administration in Madagascar, it addresses a gap in education governance literature that has largely emphasized school-level or higher education autonomy.